‘Dude, get a shot of this’: The performance of violence in the school shooting film Excursion - Bender, Stuart; Broderick, M. (Australasian Association of Writing Programs, 2016)
One of the persistent aspects of the media and general public response to campus shooting tragedies is an obsessive fascination with the motives of the killers. Our short drama Excursion attempts to intervene in this interest in the perpetrators of school shootings by displacing the emphasis from the killers to the victims and survivors. A central technique to achieve this was the profilmic performance of the actors portraying the killers: two characters who were designed as ciphers from the initial scripting stage and throughout rehearsal and filming. Where these acts of mass violence in real life can be regarded as performative in nature (Muschert & Ragnedda 2010) it is significant to consider the performance techniques employed by the actors themselves. In this article, we discuss the rehearsal and performance choices of the actors as well as the commentary by actors portraying victims and survivors of the shooting. In particular, we discuss our empirical research into the audience reaction to the two alternate endings which emphasize the performance of violence in different ways.